2019
DOI: 10.3389/feduc.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval Practice in Classroom Settings: A Review of Applied Research

Abstract: Tests have been vastly used for the assessment of learning in educational contexts. Recently, however, a growing body of research has shown that the practice of remembering previously studied information (i.e., retrieval practice) is more advantageous for long-term retention than restudying that same information; a phenomenon often termed "testing effect." The question remains, however, whether such practice can be useful to improve learning in actual educational contexts, and whether in these contexts specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 64 publications
1
80
1
4
Order By: Relevance
“…The performance difference between retrieval practice and other ways of attaining information-most commonly re-reading-is denoted as the "testing effect." The testing effect is supported by both behavioral and functional fMRI evidence (for overviews, see Dunlosky et al, 2013;van den Broek et al, 2016;Adesope et al, 2017;Antony et al, 2017;Moreira et al, 2019;Jonsson et al, 2020). Research that currently underway shows that measures of brain activity following the testing effect (retrieval practice > study) and the "CMR effect" (CMR > AR) indicate that the same brain areas are activated.…”
Section: Implications and Future Researchmentioning
confidence: 95%
“…The performance difference between retrieval practice and other ways of attaining information-most commonly re-reading-is denoted as the "testing effect." The testing effect is supported by both behavioral and functional fMRI evidence (for overviews, see Dunlosky et al, 2013;van den Broek et al, 2016;Adesope et al, 2017;Antony et al, 2017;Moreira et al, 2019;Jonsson et al, 2020). Research that currently underway shows that measures of brain activity following the testing effect (retrieval practice > study) and the "CMR effect" (CMR > AR) indicate that the same brain areas are activated.…”
Section: Implications and Future Researchmentioning
confidence: 95%
“…However, tests can also be used to enhance learning and retention. This has been demonstrated in both basic research in the laboratory (for reviews, see Karpicke, 2017; Roediger & Butler, 2011; Rowland, 2014) and applied research in educational contexts (for reviews, see Adesope, Trevisan, & Sundararajan, 2017; Dunlosky, Rawson, Marsh, Nathan, & Willingham, 2013; Moreira, Pinto & Starling, 2019). Thereby, testing can have both direct and indirect effects on long-term learning and retention (Roediger & Karpicke, 2006a).…”
Section: Introductionmentioning
confidence: 91%
“…Fourth, we may have inserted a confounding factor in our Experiment 2's design, since the number of cycles on practice phase co-varied with the difficulty, namely, four cycles for easy items and six cycles for difficult items. Karpicke and Roediger (2008) showed that, after a first correct recall of a foreign word, repeated retrieval practice is the key factor for improving memory on a delayed criterion test, probably because repeated restudy is a "shallow" encoding strategy (for a discussion about control conditions in retrieval practice literature, see Moreira et al, 2019). If only retrieval practice cycles conceive additional benefits for later memory, we may have inadvertently biased conditions in favor of difficult items in Experiment 2.…”
Section: Individual Differencesmentioning
confidence: 99%
“…We were aware that this could be a problem, but we kept this design feature in order to avoid another concern, namely, fatigue effects resulting from a rather long experiment. Future studies could extend our experiments by either (a) equally increasing both the number of successful recalls and the number of cycles for easy and difficult items, so that the items differ only in relation to the type and practice and item difficulty, or (b) comparing retrieval practice with "deeper" encoding strategies (Moreira et al, 2019).…”
Section: Individual Differencesmentioning
confidence: 99%
See 1 more Smart Citation